Hormonal contraceptive use and Staphylococcus aureus nasal and throat carriage in a Norwegian youth population - Stensen, Dina Benedicte Berg; Småbrekke, Lars; Olsen, Karina; Grimnes, Guri; Nielsen, Christopher Sivert; Simonsen, Gunnar Skov; Sollid, Johanna U. E.; Furgberg, Anne-Sofie (PLOS ONE, 2019)
Source at https://doi.org/10.1371/journal.pone.0218511. Background : Use of hormonal contraceptives has been associated with Staphylococcus aureus nasal carriage in adult women. However, the role of hormonal contraceptives in S. aureus colonization among adolescents and associations with progestin only contraceptives are unknown. Methods : We obtained nasal and throat swab samples from 439 girls aged 17–21 years in the population-based Tromsø study Fit Futures, 2012–2013, Norway, with information on lifestyle, health and biomarkers. We used multivariable logistic regression to study the association between use of hormonal contraceptives and Staphylococcus aureus carriage while adjusting for potential confounding factors. Results : Staphylococcus aureus nasal carriage prevalence were 34%, 42%, and 61% among progestin-only users, non-users, and progestin-estrogen combination contraceptive users, respectively (P<0.001). Use of combination contraceptives doubled the odds of nasal carriage (non-users reference; OR = 2.31, 95%CI = 1.43–3.74). The OR of nasal carriage was 0.29 among progestin-only users compared to combination contraceptives users (95% CI = 0.12–0.67). Discussion : In this study, use of combination hormonal contraceptives was associated with higher risk of Staphylococcus aureus nasal carriage in adolescent girls. Experimental design studies are needed to establish the role of exogenous sex steroids in Staphylococcus aureus colonization in women.